Knowledge of stroke risk factors amongst black diabetic, hypertensive and stroke patients - G. Bogoshi; A. Stewart; L. Hale; V. Fritz (AOSIS, 2003)
The objective of this study was to assess and compare the knowledge of black patients diagnosed with hypertension, diabetes and stroke about the risk factors for stroke.  Four groups made up of 33 subjects (hypertensive, diabetic, stroke and control group) were interviewed using open-ended questions and a structured questionnaire. Qualitative coding, frequencies and proportions were used to determine their knowledge.  Groups were compared with respect to percentage knowledge using the chi-square statistic at a 0.05 level of significance.  Stress was mentioned as the most important risk factor in all groups.  Although identification of stroke risk factors was  inadequate, the diabetic group was found to be significantly better in  identifying some of the risk factors (salt - p =0,05; sugar - p = 0,001; fat - p = 0,004; moderate smoking - p = 0,05; weight - p = 0,002)